DEM modeling and experimental analysis of the static behavior of a dry-joints masonry cross vaults. (10th May 2018) - Foti, D.; Vacca, V.; Facchini, I.
Graphical abstract: Highlights: Study of the dynamic and static 3D behavior of a dry-assembled masonry cross vault. Numerical modeling by mean of Distinct Element Modeling. Comparison with laboratory tests' results on a physical model obtained by mean of 3D printing. Evaluation of the three-dimensional mechanism of the cross vault. Evaluation of the ability of computational methods to predict the experimental results. Abstract: The purpose of this paper is to study the dynamic and static three-dimensional behavior of a dry-assembled masonry cross vault, through the comparison of Distinct Element Modeling results and laboratory tests' results on a physical model obtained by mean of 3D printing. The work consists of two phases: the first one compares two numerical models of a cross vault built with different masonry patterns (parallel, orthogonal); the second phase deals with a comparison between the static behavior of the computational and the real scaled models (1 m × 1 m) of the same cross vault, tested at one support collapse. The study focuses on three principal aspects: (i) to evaluate the three-dimensional mechanism of the cross vault, (ii) to determine the support displacement's magnitude that leads to its collapse and (iii) to evaluate the ability of computational methods to predict the experimental results. The results obtained from the numerical and the experimental tests have been compared in order to give general specifications on the behavior of these types of vaults.